Determinants of Savings Preferences Among Rural Villagers in Banten - Jamaludin, Nur; Mutawali; Amalia Rismanty, Vidya; Adelia, Fadillah (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2025)
This study investigates the determinants influencing saving decisions among Undrus villagers in the Banten region of Indonesia. The research examines six main factors: Islamic banking knowledge, social environment support, socialization of Islamic banks, accessibility to Islamic banks, religiosity, and understanding of the riba prohibition. Data were collected from 90 respondents selected through the Slovin method and accidental sampling technique. Employing a quantitative approach, the study utilizes multinomial logistic regression analysis using IBM SPSS 25 to explore the saving preferences among three categories: saving in Islamic banks, saving in conventional banks, and saving in neither. The findings reveal that religiosity significantly influences saving behavior, evidenced by a p-value of 0.021 (p < 0.05). The Negelkerke R² value of 0.394 indicates that the model explains 39.4% of the variance in saving preferences, while 60.6% is influenced by other factors not included in this model. This research contributes to a deeper understanding of rural saving behavior and provides insights for policymakers and Islamic financial institutions to strengthen financial inclusion and literacy in rural communities.